Annual Decline in Pentraxin 3 Is a Risk of Vascular Access Troubles in Hemodialysis Patients. (21st December 2014) - Nagai, Kei; Ueda, Atsushi; Saito, Chie; Zempo-Miyaki, Asako; Yamagata, Kunihiro
Abstract : Pentraxin 3 (PTX3), a multifunctional modulator of the innate immunoinflammatory response, is higher in patients undergoing hemodialysis than healthy control. Our study focused on annual change in PTX3 levels in patients with chronic hemodialysis, because regularly undergoing hemodialysis for many years modifies vascular inflammatory status. To demonstrate whether annual change in PTX3 is associated with vascular events, we measured blood levels of pentraxins (PTX3 and high-sensitivity C-reactive protein (hsCRP)) at baseline and in the next year in 76 hemodialysis patients and observed 20 patients with vascular access troubles during follow-up years. The annual decline in PTX3, but not hsCRP, is a significant risk of the incidence of vascular access trouble that is a critical and specific complication for hemodialysis patients (hazard ratio; 0.732 per +1 ng/mL/year in PTX3, * P = 0.039 ). This study is the first to focus on the annual change of pentraxins in a hemodialysis cohort.